Freedom: phenomenon, concept, philosophical category, “universal of culture of the subjective series” - Raida, Constantine (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2023)
The fact of presenting the phenomenon of freedom as multidimensional, and its concept as ambiguous or polysemantic, is investigated. As a phenomenon that has many varieties both in everyday life and in social and public practice. It is noted that the “dynamics” and “transformation” of various “forms” or types of freedom in public life into their opposite also gives rise to serious problems of its reproduction in philosophical thinking. The fact is recorded that in the process of historical and philosophical analysis the content and meaning of the concept of freedom has been changed historically not only depending on the development of the individual himself, society, the development of science and knowledge, but also depending on the historical development of philosophy itself, its methodological tools, ideological and conceptual foundations.